A Low Input Sustainable Fresh Market Tomato Production System - Jim R. Rich; Fred M. Rhoads; Steve M. Olson; Dan O. Chellemi (EDIS, 2003)
Fresh market tomato is an important vegetable crop in Florida. During the 1999-2000 season, the crop was grown on over 41,000 acres and was valued at over 418 million dollars. This document is ENY-678, one of a series of the Department of Entomology and Nematology, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida, Publication Date: February 2003.